Interventions to Prevent Spontaneous Preterm Birth in Women With Singleton Pregnancy Who Are at High Risk: Systematic Review and Network Meta-analysis. Issue 8 (August 2022) - Care, Angharad; Nevitt, Sarah J.; Medley, Nancy; Donegan, Sarah; Goodfellow, Laura; Hampson, Lynn; Smith, Catrin Tudur; Alfirevic, Zarko
Abstract : (Abstracted from BMJ 2022;376:e064547) The leading cause of neonatal mortality are complications due to preterm birth. To manage the risk of preterm birth, the NICE (National Institute for Health and Care Excellence) recommends using vaginal progesterone or cervical cerclage.